Cobalt‐Catalyzed Regioselective Borylation of Arenes: N‐Heterocyclic Silylene as an Electron Donor in the Metal‐Mediated Activation of C−H Bonds - Ren, Hailong; Zhou, Yu‐Peng; Bai, Yunping; Cui, Chunming; Driess, Matthias (Chemistry : a European journal, 2017)
C−H Borylation of arenes has been a subject of great interest recently because of its atom‐economy and the wide applicability of borylated products in value‐added synthesis. A new bis(silylene)cobalt(II) complex bearing a bis(N‐heterocyclic silylene)‐pyridine pincer ligand (SiNSi) has been synthesized and structurally characterized. It enabled the regioselective catalytic C−H borylation of pyridines, furans, and fluorinated arenes. Notably, it exhibited complementary regioselectivity for the borylation of fluorinated arenes compared to previously known catalytic systems, demonstrating that N‐heterocyclic silylene donors have enormous potential in metal‐catalyzed catalytic applications. Strong‐armed borylation: A new SiNSi cobalt pincer complex with two N‐heterocyclic silylene (NHSi) arms enabled the direct and facile C−H borylation of heteroarenes and fluorinated arenes with complementary regioselectivity compared to previously reported transition‐metal‐based catalysts.